Suppression of neutrophil superoxide generation by BNP is attenuated in acute heart failure: a case for 'BNP resistance'. (11th February 2015) - Liu, Saifei; Ngo, Doan T.M.; Chong, Cher‐Rin; Amarasekera, Anjalee T.; Procter, Nathan E.K.; Licari, Giovanni; Dautov, Rustem F.; Stewart, Simon; Chirkov, Yuliy Y.; Horowitz, John D.
Abstract: Aims: The release of the B‐type natriuretic peptide (BNP) is increased in heart failure (HF), a condition associated with oxidative stress. BNP is known to exert anti‐inflammatory effects including suppression of neutrophil superoxide (O2 − ) release. However, BNP‐based restoration of homeostasis in HF is inadequate, and the equivocal clinical benefit of a recombinant BNP, nesiritide, raises the possibility of attenuated response to BNP. We therefore tested the hypothesis that BNP‐induced suppression of neutrophil O2 − generation is impaired in patients with acute HF. Methods and results: We have recently characterized suppression of neutrophil O2 − generation (PMA‐ or fMLP‐stimulated neutrophil burst) by BNP as a measure of its physiological activity. In the present study, BNP response was compared in neutrophils of healthy subjects ( n  = 29) and HF patients ( n  = 45). Effects of BNP on fMLP‐induced phosphorylation of the NAD(P)H oxidase subunit p47phox were also evaluated. In acute HF patients, the suppressing effect of BNP (1 µmol/L) on O2 − generation was attenuated relative to that in healthy subjects ( P  < 0.05 for both PMA and fMLP). Analogously, BNP inhibited p47phox phosphorylation in healthy subjects but not in HF patients ( P  < 0.05). However, O2 − ‐suppressing effects of the cell‐permeable cGMP analogue (8‐pCPT‐cGMP) were preserved in acute HF. Conventional HF treatment for 5 weeks partially restored neutrophil BNP responsiveness ( n  = 25, P  < 0.05), despite no significant decrease in plasma NT‐proBNP levels. Conclusions: BNP inhibits neutrophil O2 − generation by suppressing NAD(P)H oxidase assembly. This effect is impaired in acute HF patients, with partial recovery during treatment.